2007
DOI: 10.1177/0961203307081123
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular disease in systemic lupus erythematosus

Abstract: With increasing longevity of lupus patients, peripheral vascular disease (PVD) has become an important cause of morbidity. With no systematic study of PVD in systemic lupus erythematosus (SLE), this study was undertaken to define the frequency and spectrum of PVD in SLE and factors affecting such an occurrence. All medium-sized peripheral arteries of bilateral upper and lower extremities were studied in 50 SLE patients using Doppler ultrasonography. PVD was defined clinically as one or more of intermittent cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 26 publications
6
25
2
Order By: Relevance
“…In addition, lupus has increasingly been recognized as a condition in which premature atherosclerosis develops, primarily because of increased, persistent inflammation. 6,7 Our middle-aged patient had neither a prior history of heart disease nor a positive family history, and she was also a nonsmoker and a nondiabetic. Furthermore, peripheral arterial disease usually affects lower extremities, but our patient had no intermittent claudication, and the peripheral pulses in her lower extremities were bilaterally palpable.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, lupus has increasingly been recognized as a condition in which premature atherosclerosis develops, primarily because of increased, persistent inflammation. 6,7 Our middle-aged patient had neither a prior history of heart disease nor a positive family history, and she was also a nonsmoker and a nondiabetic. Furthermore, peripheral arterial disease usually affects lower extremities, but our patient had no intermittent claudication, and the peripheral pulses in her lower extremities were bilaterally palpable.…”
Section: Discussionmentioning
confidence: 97%
“…Dyslipidemia was found to independently affect occurrence of PVD (odds ratio, OR ¼ 5.37, [95% confidence interval, CI 1.05-27.5], p ¼ 0.05). 26 Our studies have demonstrated that patients with lupus have a significantly greater IMT and greater frequency of plaques than controls. 25 The parallel increase in plaques and IMT found in our study is in contrast to some earlier studies.…”
Section: Cardiovascular Disease In Asian Patients With Lupusmentioning
confidence: 93%
“…Asian studies on atherosclerosis in SLE Higher calcium scores across all vascular beds Bhatt et al25,26 India 50 Ultrasound Carotid IMT increased, carotid plaques in 14% patients, PVD in 28% patients Ghosh et al29 India 60 Ultrasound Carotid IMT increased, FMD reduced Wolak et al35 Abu-Shakra et al 36 Israel 51 Ultrasound Atherosclerotic plaques in 28% patients versus 10% controls. FMD 13.5% in patients versus 19.3% in controls.…”
mentioning
confidence: 98%
“…Although the RP may be present in approximately 25-50% of the patients, DUs are relatively rare in SLE and they do not represent the initial manifestation of SLE (3)(4)(5). We describe here a patient with DUs and Raynaud phenomenon as the initial presentation of SLE.…”
Section: Introductionmentioning
confidence: 92%